Radiographic bone loss and the risk of medication‐related osteonecrosis of the jaw (MRONJ) in multiple myeloma patients—A retrospective case control study. (8th September 2018) - Wazzan, Taggreed; Kashtwari, Deeba; Almaden, Wejood F; Gong, Yan; Chen, Yiqing; Moreb, Jan; Katz, Joseph
Abstract: Risk factors for medication‐related osteonecrosis of the jaws (MRONJ) include type and duration of antiresorptive drugs, dental trauma, local anatomy, systemic underlying conditions and therapy, smoking, and the presence of periodontal disease. However, there is a lack of studies elucidating the role of periodontal disease as risk predictor. In the present study, the dental charts of 100 multiple myeloma (MM) patients and 16 MM patients who developed MRONJ were studied. Information about age, gender, smoking history, diabetes, steroid drug intake, type and duration of bisphosphonate (BP) treatments, MRONJ status, missing teeth, periapical lesions, widening of the periodontal ligament, and periodontal status was collected. The periodontal status was determined as a percentage of missing bone at the mesial and distal surfaces of each tooth. Multivariable logistic regression was performed to identify risk factors associated with MRONJ. In the selected model, using the COX analysis, categorical bone loss percentage is significantly associated with MRONJ ( P = 0.009), with hazard ratio 0.042 (high vs low) and 95% CI 0.004 to 0.453. Gender, steroid, Aredia BP type, and periapical are also significant in selected model. In conclusion, advanced alveolar bone loss and missing teeth were strongly related to the occurrence of MRONJ in MM patients.